Detection of human papilloma virus in normal and tumoral oropharyngeal tissue using HPV DNA in situ hybridization and p16 expression and its clinicopathologic importance - Önerci Çelebi, Özlem; Şener, Ebru; Çisel Aydın, Makbule; Güler Tezel, Gaye (ENT Updates, 2018)
Objective: The rise in the number of cancer cases with human papilloma virus (HPV)-positive squamous carcinoma of the oropharynx makes the detection of HPV clinically important. We aimed to investigate the HPV positivity in our patients who have oropharyngeal cancer and compare the two different HPV detection methods, which are HPV in situ hybridization (ISH) and p16 immunohistochemistry (IHC), and show the staining patterns. Methods: Twenty-three specimens of oropharyngeal cancer patients and ten tonsillectomy specimens that revealed no cancerous tissue (control group) were collected from retrospective file analysis. All specimens were evaluated by both p16 IHC and HPV ISH on paraffin blocks. Results: Seven of 23 cases showed p16 expression. Of all these 7 cases that showed p16 expression, six showed high p16 expression and one showed low p16 expression. All six cases that showed high p16 expression were HPV ISH (+). One case that showed low expression of p16 was HPV ISH (-). All cases that were p16 (+) showed diffuse p16 expression and none of the cases showed focal p16 expression. Conclusion: High p16 expression (>70%) is a reliable marker of HPV positivity. Combining p16 IHC with HPV ISH will further improve its specificity. All p16 positive cases showed diffuse p16 expression, thus did not show tumor heterogeneity, suggesting that even a biopsy specimen showing diffuse p16 expression shows p16 positivity of the whole tumoral tissue.